Physical Activity Impairment in Depressed COPD Subjects. - Di Marco, Fabiano; Terraneo, Silvia; Roggi, Maria Adelaide; Repossi, Alice C; Pellegrino, Giulia M; Veronelli, Anna; Santus, Pierachille; Pontiroli, Antonio E; Centanni, Stefano (Respiratory Care, 2014)
BACKGROUND: Limited exercise tolerance is a cardinal clinical feature in COPD. Depression and COPD share some clinical features, such as reduced physical activity and impaired nutritional status. The aim of the present study was to evaluate maximum and daily physical activities and the nutritional status of COPD patients affected or not by depression. METHODS: In 70 COPD out-patients, daily and maximum physical activities were assessed by multisensor accelerometer armband, 6-min walk test, and cardiopulmonary exercise test. Mental status, metabolic/muscular status, and systemic inflammation were evaluated using the Hospital Anxiety and Depression Scale, by bioelectrical impedance analysis, and with regard to fibrinogen/C-reactive protein, respectively. RESULTS: Depressed subjects (27% of the sample) showed a similar level of respiratory functional impairment but a higher level of shortness of breath and a worse quality of life compared to non-depressed subjects (P < .05). Specifically, they displayed a physical activity impairment consisting of a reduced number of steps per day, a lower peak of oxygen consumption, an early anaerobic threshold, and a reduced distance in the 6-min walk test (P < .05) but the same nutritional status compared to non-depressed subjects. In the multivariate analysis, a reduced breathing reserve, obesity, and a higher level of shortness of breath, but not depression, were found to be independent factors associated with a reduced daily number of steps. CONCLUSIONS: Our study found that depressed COPD patients have a reduced daily and maximum exercise capacity compared to non-depressed patients. This further suggests the potential utility of screening for depression in COPD.